1998
DOI: 10.1095/biolreprod59.1.160
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Studies on the In Vitro Decidualization Process in the Baboon (Papio anubis) and Human1

Abstract: The process of decidualization involves the morphological and functional transformation of stromal fibroblasts to decidual cells. The objective of this study was to define appropriate in vitro culture conditions required for decidualization of baboon stromal cells. Parallel studies were also done with human endometrial stromal cells for comparative analysis. Human stromal cells produced prolactin and insulin-like growth factor-binding protein (IGFBP)-1 in response to hormones (estradiol-17beta [36 nM], medroxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 33 publications
4
69
0
Order By: Relevance
“…Immunostaining of serial sections obtained in this study with a monoclonal antibody to ␣SMA (14,20) showed that the stromal fibroblasts directly below the epithelial plaques and luminal epithelium of hCGtreated baboons stained intensely for ␣SMA (Figs. 2C and 3C).…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…Immunostaining of serial sections obtained in this study with a monoclonal antibody to ␣SMA (14,20) showed that the stromal fibroblasts directly below the epithelial plaques and luminal epithelium of hCGtreated baboons stained intensely for ␣SMA (Figs. 2C and 3C).…”
Section: Resultsmentioning
confidence: 66%
“…The sense primer sequence was 5Ј-CCC CCA GAC CAA GCA GGA CCT GGA GCT CCC 3-Ј, and the antisense primer was 5Ј-ATC GTC CTG CAC CAG GAC TCT GGC CAG GTA-3Ј. The histone 3.3 PCR product was coamplified with glycodelin and served as an internal standard (20).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PCR primers specific for osteopontin (according to Zhang et al 2004; 169 bp product), fatty acid binding protein-4, FABP-4 (according to Larson et al 2004;387bp product), and collagen II (according to Zhang et al 2004; 394 bp product) were used in 50pmol concentration. The constitutively expressed histone H3.3 was used in 10 pmol primer concentration (primers according to Kim et al 1998). PCR products were created using 32 cycles consisting of at 94 °C (1min), then 60 °C (55 °C for osteopontin) (2min), then 72 °C (3min), followed by 15 min of final extension at 72 °C.…”
Section: Reverse Transcription-polymerase Chain Reaction (Rt-pcr) Detmentioning
confidence: 99%
“…Differentiation into decidual cells is important for control of endometrial vascularization and involves vasodilation and angiogenesis in the endometrium [48]. During the process of decidualization, endometrial stromal fibroblasts transform morphologically and biochemically into polygonal, secretory cells and begin to express specific decidual proteins such as prolactin and insulin like growth factor binding protein-1 (IGFBP-1) [49]. Although the morphological changes are useful predictors of successful implantation, the molecular mechanisms underlying them are largely unknown and remain to be elucidated.…”
Section: Window Of Uterine Receptivitymentioning
confidence: 99%